The Effect of Problem Based Learning Models On Students' Cognitive Learning Outcomes in Environmental Change Material - Fitria Nasution; Abdul Hakim Daulae2 (UNIVERSITAS PGRI MADIUN, 2026)
This study aims to determine the effect of the Problem Based Learning model on students' cognitive learning outcomes in environmental change material. This study was conducted from May to August 2025 at SMA Negeri 4 Medan. The research design used was a quasi-experimental design. The design used was a pretest-posttest design with a control group, using simple random sampling techniques. The samples in this study were X1 as the experimental class and X3 as the control class. Based on the research results, the average pretest score for the experimental class was 59.429 and the average posttest score was 84.143. Meanwhile, in the control class, the average pretest score was 58.714 and the average posttest score was 74.714. Based on the results of the independent t-test, a significance level (2-tailed) of 0.000 was obtained. Thus, this significance value is smaller than the significance level of 0.05 (0.000 < 0.05), so the null hypothesis (H₀) is rejected and the alternative hypothesis (Ha) is accepted. Therefore, it can be concluded that there is an effect of the problem-based learning model on student learning outcomes in the cognitive domain of environmental change material at SMA Negeri 4 Medan.